Should I Stay or Should I go? The Influence of Handling by Researchers on Den use in an Arboreal Nocturnal Rodent. (5th August 2013) - Kukalová, Monika; Gazárková, Anežka; Adamík, Peter
Abstract: Understanding how animals respond to disturbance by investigators is essential for a fair assessment of the presence of bias in routinely used research protocols. It is also an essential prerequisite for anyone interested in animal welfare and ethically sound research. Here, we utilize an automatic logging system to monitor nest box use by PIT‐tagged edible dormice, Glis glis, after standard handling procedures applied during a regular nest‐box monitoring programme. The edible dormouse is an arboreal nocturnal rodent that relies on tree hollows as daytime den sites. We assessed the effect of disturbance on dormice in two ways: whether it affected the decision of an individual to stay in the same den site for a subsequent day and whether it affected the timing of the individual's nocturnal emergence from the den site. We found handling had a strong negative effect on short‐term den use. In addition, females and sexually active individuals were more likely to spend the following day in the nest box. Individuals that had left the den site after our handling returned to them after an average of 4 d. Handling did not have a significant effect on the period of absence, but reproductively active animals returned on average after 3 d, while reproductively quiescent animals returned after more than 5 d. Manipulation did not have a significant effect on the initiation of nocturnal activity. Our study suggests that disturbance by investigators may modify certain aspects of animal behaviour, but this effect is likely to be short term and does not appear to impair the efficacy of routinely practiced capture‐mark‐recapture field protocols.